2006
DOI: 10.1149/1.2196671
|View full text |Cite
|
Sign up to set email alerts
|

Low-Voltage Electrodeposition of Fullerol Thin Films from Aqueous Solutions

Abstract: A low-voltage ͑Ͻ2 V, three-electrode system͒ method for the cathodic electrodeposition of fullerol ͓polyhydroxylated fullerene, C 60 ͑OH͒ n ͔ from an aqueous solution has been developed for the synthesis of thin films. Scanning electron microscopy of the electrodeposited fullerol films shows that the films are microscopically uniform; the film thickness was observed to vary linearly with the deposition charge. X-ray photoelectron spectroscopy of the C 1s peak indicates that the carbon constituents of the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Their biological efficiency depends on both the modification on the cage and the cage size (C 60 , C 70 , C 82, etc.). To date, pristine C 60 and their functionalized derivatives have been fully investigated and commercialized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Their biological efficiency depends on both the modification on the cage and the cage size (C 60 , C 70 , C 82, etc.). To date, pristine C 60 and their functionalized derivatives have been fully investigated and commercialized.…”
Section: Introductionmentioning
confidence: 99%
“…Fullerenes, one category of the most popular carbon nanomaterials, have been widely used in solar energy, cosmetics, personal care, electronics and biomedicine due to their unique chemical and physical properties. [1][2][3][4][5][6][7] Their biological efficiency depends on both the modication of the cage and the cage size (C 60 , C 70 , C 82 , etc.). To date, pristine C 60 and its functionalized derivatives have been fully investigated and commercialized.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, fullerol films are under investigation for possible use in the conversion of solar energy. 19…”
Section: Introductionmentioning
confidence: 99%
“…This functionalization can change the solubility of these compounds from less than 10 −9 mg/L for C 60 to >50 mg/L for fullerols. , Higher derivatized C 60 fullerols with a solubility of 6 g/L also have been reported . These fullerols are under investigation for use in biomedical applications, due to their antioxidant abilities and also are in development as drug carriers for their ability to bypass protective bodily interfaces, including the blood−retina and the blood−brain barriers. Using different modifications, water-solubilized fullerenes were also found to possess antioxidative, antibacterial, and antiviral properties, thereby opening up a wide range of possible applications. In addition, fullerol films are under investigation for possible use in the conversion of solar energy …”
mentioning
confidence: 99%
“…Scanning electron and atomic force microscopy of EL films fabricated by deposition of metal ions from an adjacent flowing bulk fluid indicate that flow-enhanced deposition could offer improved film continuity and reduced variability in thickness . Flow-enhanced deposition could be utilized in electrodeposition, for which the nanoscale deposition rate varies due to edge effects, local variations in current due to changes in deposited metal thickness, and electrode variation with time. ,− However, it has been reported that very thin films deposited by EL plating are not uniform because the initial deposition is confined to discrete nucleation sites that grow laterally and coalesce into a continuous film . Mechanistically, EL Au deposition from aqueous sodium Au(I) sulfite occurs by galvanic displacement of Ag on tin (Sn)-wetted substrates.…”
Section: Introductionmentioning
confidence: 99%